REALIA AS A CULTURAL PHENOMENON - Egamberdiyeva Irodaxon; Shahobidinov Obidjon (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: In this article, you can learn about origin of realia and its history. As well as to translate it in understandable way to others who are from another culture and country.